2019
DOI: 10.1108/jgm-06-2019-070
|View full text |Cite
|
Sign up to set email alerts
|

The dark side of expatriation: dysfunctional relationships, expatriate crises, predjudice and a VUCA world

Abstract: The dark side of expatriation: dysfunctional relationships, expatriate crises, predjudice and a VUCA world Introduction International assignments and other forms of global employment continue to increase in numbers and complexities (Brookfield Global Relocation Services, 2017;Dickmann, 2018). The high practical relevance of this topic is reflected in the extensive research and tremendous wealth of knowledge about global mobility that has accumulated over the past few decades (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Extant literature has identified expatriate supervisors as the "ideal boss" (e.g., Selmer, 1996) whereas other studies have suggested that HCNs are essential to foster expatriate success (Toh & DeNisi, 2007). For example, Bader et al (2019) concluded that expatriate supervisors may negatively affect HCNs' affective commitment, which may however be influenced by HCNs' values. The RL lens has the potential to elucidate these rather opposing views since it goes beyond the leader-follower dyad and centers on the broader context in which expatriation occurs, and in this way focuses on supervisors' engagement with stakeholders both inside and outside the organization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant literature has identified expatriate supervisors as the "ideal boss" (e.g., Selmer, 1996) whereas other studies have suggested that HCNs are essential to foster expatriate success (Toh & DeNisi, 2007). For example, Bader et al (2019) concluded that expatriate supervisors may negatively affect HCNs' affective commitment, which may however be influenced by HCNs' values. The RL lens has the potential to elucidate these rather opposing views since it goes beyond the leader-follower dyad and centers on the broader context in which expatriation occurs, and in this way focuses on supervisors' engagement with stakeholders both inside and outside the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Across cultures, fundamental values and virtues are likely to differ (Szőcs & Miska, 2020), making cross-cultural adjustment even more challenging. Correspondingly, Bader et al (2019) pointed to important unanswered questions in global mobility research, such as to what extent an individual's values and ethics might change when abroad or how expatriates are affected by and deal with value clashes. These issues are particularly apposite when considering the "dark" side of expatriation, where value dissimilarities may incline expatriates toward unethical practices in host countries.…”
Section: Cross-cultural Adjustmentmentioning
confidence: 99%
“…While a few studies have applied the JD-R theory in the migration (Qin et al, 2014), repatriation (Ren et al, 2014) and expatriation context Lazarova et al, 2010), no study has yet empirically tested a set of demands and resources and their impact on work-related outcomes for expatriates working in environments considered to be particularly stressful. A focus on not only positive work-related outcomes (wellbeing, engagement) but also the darker side (in JD-R research often represented as burnout) would be relatively new in the scholarly debate on expatriates (Bader et al, 2019b). Possibly the inclusion of personal demands and resources might be particularly insightful in context where the expatriates' work and private spheres are blurred and research shows that non-work constraints have a more profound impact on the expatriate's wellbeing (see Bader et al, 2016).…”
Section: Discussion Future Research and Contributionmentioning
confidence: 99%
“…well-being, engagement) but also the darker side (e.g. burnout) would be relatively new in the scholarly debate about expatriates (Bader et al , 2019b). It would reflect the logic of detrimental effects (i.e.…”
Section: Discussion Future Research and Contributionmentioning
confidence: 99%
“…HAOs are not able to comply as easily with these field expectations. They display what Bader et al (2019) describe as a typical area of conflict: compliance versus adjustment in a volatile, uncertain, complex and ambiguous (VUCA) environment, as it applies to the disaster relief environment. Their highly unpredictable environment requires flexible handling with staffing expectations which seems to be the basis of legitimation in the field (see Figure 2).…”
Section: Theoretical Implicationsmentioning
confidence: 99%